196 Multi-omic Convergence of Human Craniosynostosis Genes Within a Developmental Bone-Dura-Brain Nexus. (1st April 2022) - Kiziltug, Emre; Allington, Garrett; Kawaguchi, Riki; Panchagnula, Shreyas; Geschwind, Daniel; Kahle, Kristopher
Abstract : INTRODUCTION: Craniosynostosis (CS) is the premature fusion of the calvarial sutures and has long been considered mostly an aesthetic disorder, despite many affected children experiencing neurocognitive deficiencies and seizures. The two types of CS, syndromic and non-syndromic, present with significant genetic clinical heterogeneity, suggesting a complex interplay of genetic and environmental causes. Given the neurodevelopmental symptoms observed in CS patients, we hypothesized the genes involved in the pathophysiology of CS may play a key role in the functional development of the brain. METHODS: We applied a multimodal integrative genomic approach to examine the functional relationships as well as the spatiotemporal and cellular interactions of all currently known craniosynostosis-associated genes (CSGs) and also explored whether they are linked to other neurodevelopmental disorders (NDD). To this end, we constructed gene co-expression modules using a bulk-RNA expression dataset with 27 human brains encompassing 16 human brain regions across fetal development into early childhood. We further used scRNA-seq datasets derived from embryonic mouse meninges, calvarial sutures and developmental human brain to identify cell-types enriched with CSGs. RESULTS: The set of co-expression modules significantly enriched with CSGs were highly expressed during mid-gestation and in primary motor, somatosensory and prefrontal cortices, and the ganglionic eminence. Moreover, some of these modules were also significantly enriched with autism-spectrum disorder (ASD) and NDD genes. The most significant modules were associated with histone-3 lysine-4 methylation, neural crest differentiation, endochondral ossification and reactive astrogliosis. The mouse meninges scRNAseq analysis showed enrichment in pial and dural fibroblasts. The whole-brain scRNA-seq analysis showed CSGs were enriched in medial ganglionic eminence (MGE)-derived cortical interneurons, astrocytes and oligodendrocyte precursors during mid-fetal brain development. CONCLUSION: CSGs may contribute to pathogenesis through epigenetic dysregulation, disrupted neural crest differentiation facilitated by neuroglial cells and MGE interneuron migration very early during development. These processes are in confluence with premature suture fusion mediated by dural and pial fibroblasts.